When seeing isn't believing [multimedia authentication technologies]. - Zhu, B.B.
Digital multimedia is ubiquitous today. Multimedia is easily reproduced and modified without any trace of manipulations. In most cases, a human will not be able to judge whether a multimedia signal is authentic by perceptual inspection. In this article we provide a compact yet fairly comprehensive introduction of multimedia authentication (MA) to the general signal processing audience. The article gives a brief discussion on the different MA technologies such as hard authentication, soft authentication, quality-based authentication, content-based authentication, block authentication, and lossless watermarking.
Keywords: Block authentication; Content-based authentication; Digital multimedia; Hard authentication; Lossless watermarking; Multimedia authentication technologies; Quality-based authentication; Signal processing; Soft authentication